ANALISIS METODE BERNYANYI TERHADAP PERKEMBANGAN EMOSIONAL PADA ANAK USIA DINI - nofiafitranasari nofiafitranasari; Indra Yeni Yeni (Early Childhood: Jurnal Pendidikan, 2021)
This study aims to examine the singing method on emotional development in early childhood. The method used in this research is literature study, by examining the reading sources. The technique of collecting data is in the form of study and review of several data sources for several relevant reading references, such as scientific journals, articles, bulletin and previous research and relevant reference books. Furthermore, data analysis is carried out by connecting the problem with the relevant theory. The results of the research findings can prove that the singing method can improve the development of emotional intelligence in children in terms of controlling feelings of anger, controlling feelings of fear, controlling feelings of pleasure and feelings of sadness with excellent and optimal results. This shows that the singing method in the development of the emotional aspects of children has a huge influence on the future. By paying attention to the steps of the correct singing method. Formulate the main content of the material being taught. Describe correctly any information or concepts and material facts that must be mastered. Determine the tone of the song that is often used in the child's environment. Formulate factual information on material concepts that will be mastered by children in the form of song lyrics, then adjust to the tone of the song to be selected. The teacher must first practice the song to be sung. Demonstrate together with children repeatedly. Followed by gestures that match the rhythm and lyrics of the song. Provide questions and answers about the message conveyed in the song. It can be concluded that using the singing method in a learning activity is an activity that is very popular with children and can develop all aspects of development including emotional aspects